2020
DOI: 10.1002/csr.1939
|View full text |Cite
|
Sign up to set email alerts
|

Linking human values to consumer CSR perception: The moderating role of consumer skepticism

Abstract: This paper examines the effect of human values on consumer CSR perception towards cosmetic companies. Since consumer skepticism is on the rise, its moderating effects are also investigated in this paper. Questionnaires were collected from 479 consumers of seven cosmetic companies which were subsequently analyzed via structural equation modelling. Findings revealed that human values such as self‐enhancement and openness to change have a significant influence on consumer CSR perception. Consumer skepticism was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 105 publications
(172 reference statements)
1
21
0
Order By: Relevance
“…According to Hansen et al (2018), openness to change includes stimulation and self-direction values. Individuals with a high level of openness to change view the consumption of natural food products as an opportunity for progress (Ramasamy et al, 2019). Tiainen et al (2013) further demonstrated the favourable relationship between openness to change and healthy eating habits; people who score high on openness to change consume more nutrients and exhibit fewer unhealthy eating behaviours.…”
Section: Extending Basic Human Values Theory and Sor Theory To The Pr...mentioning
confidence: 97%
See 2 more Smart Citations
“…According to Hansen et al (2018), openness to change includes stimulation and self-direction values. Individuals with a high level of openness to change view the consumption of natural food products as an opportunity for progress (Ramasamy et al, 2019). Tiainen et al (2013) further demonstrated the favourable relationship between openness to change and healthy eating habits; people who score high on openness to change consume more nutrients and exhibit fewer unhealthy eating behaviours.…”
Section: Extending Basic Human Values Theory and Sor Theory To The Pr...mentioning
confidence: 97%
“…Openness to change is associated with individuals' thoughts, feelings, actions and propensity to accept novel experiences (Tiainen et al, 2013;Hansen et al, 2018;Ramasamy et al, 2019). Underscoring its importance, Schwartz and Sagiv (1995) called openness to change a higher order value.…”
Section: H1 Universalism Is Positively Associated With Brand Trustmentioning
confidence: 99%
See 1 more Smart Citation
“…We examine if millennials as prospective applicants perceive the motive underlying organizations' CSR engagement, and the study seek to understand whether CSR motive perception plays any role in the indirect relationship between CSR and millennial's intention to seek employment with an organization. This is because it has become crucial for organizations to show the sincerity of CSR engagements, to manage inconsistencies regarding organizational CSR motives, and garner favorable millennial joining disposition (Ramasamy, Dara, Amran, & Nejati, 2020).…”
Section: Purpose and Significance Of The Studymentioning
confidence: 99%
“…PA has recently been emphasized by scholars in understanding stakeholders' engagement with organizational CSR, since company-seeking motives have not always been met with favorable stakeholder perception but increased CSR skepticism (Rim, Park, & Song, 2020). Stakeholders' perception of CSR motives as altruism is more likely to lower CSR skepticism (Ramasamy et al, 2020). Other researchers have, on the contrary, argued that however altruistic an organization's CSR behavior may seem, it is in core driven by company interest (Carlson & Zaki, 2018).…”
Section: Pa Of Csrmentioning
confidence: 99%